PEMIKIRAN DAN PERADABAN ISLAM DI ASIA TENGGARA: Tinjauan Historis Terhadap Proses Islamisasi dan Tranformasi Sosial Budaya Proses Islamisasi dan Tranformasi Sosial Budaya - Farhan Maulana Arli (UIN Sumatera Utara, 2026)
This study is motivated by the importance of understanding the distinctive characteristics of Islam in Southeast Asia, which developed in a peaceful and adaptive manner, as well as the limited attention given to the role of education in the Islamization process. The study aims to analyze the history of the arrival of Islam, the development of Islamic thought, the formation of Islamic civilization, and the influence of colonialism and modernization in the region. This research employs a qualitative approach through a literature review of various scholarly sources. The findings reveal that Islamization occurred through trade, marriage, and Sufism, and was systematically strengthened by educational institutions. Islamic thought in Southeast Asia developed in a moderate and contextual manner, while Islamic civilization emerged through the integration of Islamic values with local cultures. Colonialism and modernization posed significant challenges but also stimulated intellectual renewal and reform. In conclusion, Islam in Southeast Asia has evolved into an inclusive and dynamic civilization, with education serving as a key factor in sustaining its continuity and relevance in the modern era.Keywords: Islam in South-East Asia, Islamic Thought, Islamic Civilisation, Islamisation, Islamic Education